THE PROJECTION OF INDONESIA POPULATION BASED ON STOCHASTIC DIFFERENTIAL EQUATION ( SDE ) - EFENDI (CV KULTURA DIGITAL MEDIA, 2020)
This paper was studied the application of stochastic differential equations to predict the Indonesian population. The data is the Indonesian census from 1930 to 2010 published by The Indonesian Census Board, and were simulated using Maple software. The result is the Indonesian population growth depends on population growth rate. In the simulation, the growth rate was assumed to vary from 1.4 % to 1.8 %. The result is similar to BKKBN prediction published on Thursday 3 October 2015, that people reached 345 million or more